2021
DOI: 10.1186/s10020-021-00277-4
|View full text |Cite
|
Sign up to set email alerts
|

Clara cell 16 KDa protein mitigates house dust mite-induced airway inflammation and damage via regulating airway epithelial cell apoptosis in a manner dependent on HMGB1-mediated signaling inhibition

Abstract: Background House dust mite (HDM) inhalation can cause airway epithelial damage which is implicated in the process of airway inflammation in asthma. High mobility group box 1 (HMGB1) is critically required for cellular damage and apoptosis as an important endogenous danger signal. Recently, Clara cell 16KDa protein (CC16) has been identified to exert anti-inflammatory and immunomodulatory influence in various injury-related diseases model. However, little is known about its ability to protect ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…A study recently reported HMGB1 upregulation in HDM-induced asthmatic rats, HMGB1 overexpression aggravated HDM-induced inflammatory responses and airway damage ( 12 ). Herein, we investigated whether Alutard SQ could regulate HMGB1 expression in HDM-challenged asthma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study recently reported HMGB1 upregulation in HDM-induced asthmatic rats, HMGB1 overexpression aggravated HDM-induced inflammatory responses and airway damage ( 12 ). Herein, we investigated whether Alutard SQ could regulate HMGB1 expression in HDM-challenged asthma.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of HDM inhalation and airway epithelial cells directly caused airway epithelium dysfunction. HDM stimulates airway epithelial cells to release epithelial-derived cytokines, and recruit neighboring innate and adaptive immune cells including DCs, T-cells (such as Th2, Th1, and Th17), B-cells, eosinophils, and neutrophils, which are essential for asthma pathogenesis ( 12 , 30 , 31 ). Amongst these cytokines, IL-13, IL-33, TSLP, CCL5, CCL7, CCL17, CCL22, IFN-γ, IL-4, and several eotaxins strongly direct or support the development of a Th2 polarized inflammation ( 30 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…We were curious about whether there are links between DEP-inhibited CC16 secretion in epithelial Clara cells and DEP-induced the inflammatory response in BEAS-2B airway epithelial cells without CC16 expression? Increasing evidence showed that CC16 protects airway epithelial cells from environmental stimuli, such as house dust mite and cigarette smoke exposure [20][21][22]. Herein, the role of CC16 in bronchial epithelial cells exposed to DEP was investigated.…”
Section: Agingmentioning
confidence: 99%
“…It is well known that CC16 has anti-inflammatory and antioxidant effects [14][15][16][17][18][19]. The change in CC16 level not only has a profound effect on the composition of the airway surface fluid, but also affects the response of the airway epithelium to environmental stimuli [20][21][22]. For instance, CC16 mitigates house dust miteinduced airway inflammation and damage via regulation of airway epithelial cell apoptosis [20]; and CC16 level is also correlated with cigarette smoke exposure in bronchial epithelial cells, and protects against lung injury in smokers [21].…”
Section: Introductionmentioning
confidence: 99%
“…Measuring the CC16 concentration makes it possible to assess a degree of Club cell damage, and, therefore, the magnitude of respiratory epithelium damage and bronchial dysfunction [9]. Given the above, growing attention has been paid in the scientific literature to the research of new laboratory markers for diagnostics of bronchiolitis in young children.…”
Section: Introductionmentioning
confidence: 99%